ROLE OF 'NARI SHAKTI VANDAN ACT 2023' IN WOMEN EMPOWERMENT - Mehta, Sakshi; Tiwari, Varsha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
When women take up any responsibility, they put in all their efforts to take the resolution to accomplishment. The biggest benefit of the Nari Shakti Vandan Act 2023 law will be that this law will create a lot of confidence in the women power of the country. The passion to work for the country, the power to take India forward will increase manifold. The project started by tribal women has today become a competitor to multinational companies, which introduces the women power of India. The country is going to benefit from this skill of women, their leadership in the coming days. The importance of women power has also been seen in Parliament. All the political parties of India have had to support this ordinance. Today, from family to panchayat, from economy to education and enterprise, women power is doing unprecedented work in every field. Women have played a very big role in taking India to the moon. Today, be it startups, self-help groups, or social campaigns like cleanliness, the participation and role of women is becoming the strength of the country. The Nari Shakti Vandan Act 2023 passed as the 128th amendment to the Indian Constitution seeks to empower the political participation of women by increasing the seats reserved for them in the Indian Parliament. This amendment aims to promote women's representation and make them more inclusive in decision-making processes.